Tin man - O'Connor, Matthew; O'Connor, Michael; Blotevogel, Jill E.; Mitchell, Steven Long.; Van Sickle, Craig W.; Willing, Nick.; Deschanel, Zooey, 1980-; Cumming, Alan, 1965-; McDonough, Neal.; Robertson, Kathleen, 1973-; Trujillo, Raoul; Rennie, Callum Keith, 1960-; et al. (Santa Monica, Calif. : Genius Entertainment, 2008)
Dorothy Gale, a.k.a. DG, is all grown up and bored. She mopes around working as a waitress and goes to school part time. Before she knows it, she's back in OZ and on the run from the evil sorceress Azkadellia, her storm troopers and clumsy bats. Along the way she falls in with some strange characters including the brainless Glitches; Raw, a cowardly and psychic lion-man hybrid; and, Wyatt Cain, a cowboy cop from Central City called a 'tin man' because of his tin badge.
English track: Dolby digital 5.1
Title from container.
Special features: 'Beyond the Yellow Brick Road', behind-the-scenes look; on the set with the director; 'wizard tricks', gag reel; 'The brain, heart and courage of the movie', interviews with the cast and crew.
Director of photography, Thomas Burstyn ; editor, Allan Lee ; music, Simon Boswell ; costume designer, Angus Strathie ; production designer, Michael Joy.
Zooey Deschanel, Alan Cumming, Neal McDonough, Kathleen Robertson, Raoul Trujillo, Callum Keith Rennie, Anna Galvin, Ted Whittall, Richard Dreyfuss.
Not rated.
Keywords: Gale, Dorothy -- (Fictitious character) -- Drama; Witches -- Drama; Psychics -- Drama; Police -- Drama; Feature films; Fantasy films; Action and adventure films; Science fiction films; Feature films; Fantasy films; Science fiction films; Action and adventure films